Mismatch repair gene expression in gastroesophageal cancers - Dracea, Amelia; Angelescu, Cristina; Danciulescu, Mihaela; Ciurea, Marius; Ioana, Mihai; Burada, Florin (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Mismatch repair (MMR) genes play a critical role in maintaining genomic stability, and the impairment of MMR machinery is associated with different human cancers, mainly colorectal cancer. The purpose of our study was to analyze gene expression patterns of three MMR genes (MSH2, MHS6, and EXO1) in gastroesophageal cancers, a pathology in which the contribution of DNA repair genes remains essentially unclear. Materials and Methods: A total of 45 Romanian patients diagnosed with sporadic gastroesophageal cancers were included in this study. For each patient, MMR mRNA levels were measured in biopsied tumoral (T) and peritumoral (PT) tissues obtained by upper endoscopy. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) with specific TaqMan probes was used to measure gene expression levels for MSH2, MSH6, and EXO1 genes. Results: A significant association was observed for the investigated MMR genes, all of which were detected to be upregulated in gastroesophageal tumor samples when compared with paired normal samples. In the stratified analysis, the association was limited to gastric adenocarcinoma samples. We found no statistically significant associations between MMR gene expression and tumor site or histological grade. Conclusion: In our study, MSH2, MSH6, and EXO1 genes were overexpressed in gastroesophageal cancers. Further investigations based on more samples are necessary to validate our findings.